Bone Pipes with Parallel Tone Holes. Materials from Medieval Poland (until the End of the 12th C) - Dorota Popławska (EXARC, 2021)
Bone and wood pipes are among the medieval aerophones which have been discovered during archaeological excavations in Poland. The ones that interested us are characterized by a parallel arrangement of sound holes. They are short pipes, several centimetres long, with two holes cut in different places of the pipe body, either at one end or in the middle. There are pipes with three or even four holes cut in two rows. According to Włodzimierz Kamiński and Tadeusz Malinowski they were two-tone musical instruments due to having two tone holes (Kamiński, 1971, 46; Malinowski 1996, 24). The subject matter of this study is the verification of this hypothesis. Three pipes were subjected to sound experiments by professional musicians using replicas of such pipes, made with bone and elderwood. During the tests the possibilities of the embouchure (various positions of lips, tongue, teeth and facial muscles) were examined: as seen with flute, oboe and clarinet. The test results showed that the objects are used as reed pipes rather than a flute pipe.